2021
DOI: 10.17582/journal.sja/2021/37.s1.09.15
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and Morphometric Characterization of Hycole, Hyla and New Zealand White Rabbits for KUAT Hybrid (Tropical Adaptive and Superior Rabbit)

Abstract: Importations were done to overcome raising demand on broiler rabbit. Hycole, Hyla and New Zealand White rabbits have a superiority on high growth rate and prolification rate. The body weight of Hyla's rabbit in the age of 70 d can reach 2 160 g (de la Abstract | Hycole and Hyla rabbits were imported in 2012 and 2013. Hycole and Hyla rabbits were known as best broiler rabbit and had potentiality as genetic resources to develop Indonesian broiler rabbit. The aim of this study was to characterize phenotype of Hyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
(21 reference statements)
1
2
0
2
Order By: Relevance
“…The authors have cited different factors like sex, genetic type, environmental conditions and different management conducted by the farmers. In the same context, Brahmantiyo et al (2021), studied morphological characteristics of Hycole, Hyla and New Zealand white rabbits aged 20 weeks old and they found longer DL, EL, EW, head height, chest depth, Radius Ulna, and Femoris than the present paper. The same study has observed a significant effect (P<0.05) of GxS interaction on some body traits like: head height, length and width of the ear, chest depth, radius ulna length, and the length of the spine.…”
Section: Morphological Traitssupporting
confidence: 49%
“…The authors have cited different factors like sex, genetic type, environmental conditions and different management conducted by the farmers. In the same context, Brahmantiyo et al (2021), studied morphological characteristics of Hycole, Hyla and New Zealand white rabbits aged 20 weeks old and they found longer DL, EL, EW, head height, chest depth, Radius Ulna, and Femoris than the present paper. The same study has observed a significant effect (P<0.05) of GxS interaction on some body traits like: head height, length and width of the ear, chest depth, radius ulna length, and the length of the spine.…”
Section: Morphological Traitssupporting
confidence: 49%
“…En cuanto a la LF, coinciden con los datos de trabajos con NZB (Masoud et al, 1986;Gafni et al, 2001;Martiniaková et al, 2008;Cardinali et al, 2015), otras razas y cruzas (Gondret et al, 2005;Michalik et al, 2006;Dalle-Zotte et al, 2009;Xiccato et al, 2013;Matics et al, 2018). Aunque, otros estudios se ha notado superioridad de estas medidas debido a la crianza en zonas templadas (Lukefahr y Ozimba, 1991) y mejoramiento genético (Brahmantiyo et al, 2021). Los valores de LT-P entran dentro del plano de datos provistos en conejos NZB (Latimer y Sawin, 1962;Masoud et al, 1986) así como otras razas y cruzas de talla medianas (Gondret et al, 2005;Szendrö et al, 2010;Buijs et al, 2012;Dalle-Zotte y Paci, 2014).…”
Section: Rasgos Del Pv Pcc Y Medidas Osteométricasunclassified
“…En el conejo, estas características de crecimiento dimensional de los huesos, se comienzan a estabilizar entre seis a ocho meses de edad (Masoud et al, 1986;Zoetis et al, 2003;Willett et al, 2011). No obstante, tales variaciones pueden ser afectadas por factores como la edad, raza, etapa fisiológica, sexo, alimentación y clima (Yalçın et al, 2006;Martiniaková et al, 2008;El-Kady et al, 2021;Brahmantiyo et al, 2021).…”
Section: Introductionunclassified
“…Other advantages of keeping rabbits over other livestock species include limited cost of the housing, feeding, efficient reproductive ability, efficient feed converter, ability to live on forage requires little space compared to other large livestock, especially in areas where there are shortage of agricultural land. They are easy to transport and market (Biobaku and Oguntona, 2007;Brahmantiyo, et al, 2021;Nathaniel, et al, 2023). Apart from being a good source of white meat, rabbits provides fur, skins, manure and pets.…”
Section: Introductionmentioning
confidence: 99%